Civic Responsibility di Era Krisis Iklim: Integrasi Pendidikan Kewarganegaraan dengan Kesadaran Lingkungan: Civic Responsibility in the Era of Climate Crisis: Integrating Citizenship Education with Environmental Awareness - Ahmad Muhamad Mustain Nasoha; Yahya Fadhlullah Murtaja; Ridwan Alvin Saputra; Afif Abdus Syakur; Faa’iz Zainul Muttaqin (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The climate crisis is a global issue that demands everyone to take a role and take action towards the environment for its sustainability. Therefore, in this context, civic responsibility is not limited to social and political matters but also encompasses ecological responsibilities and must be internalized in educational practices. This study aims to accelerate the integration of civic education and environmentally conscious citizenship, which is one step to affirm civic responsibility amid the climate crisis. This study uses a qualitative method through a library study that examines several educational institutions, learning practices, and policies related to citizenship, the environment, and environmental learning. The results obtained indicate that civic education has great potential in developing critical awareness, active participation, and responsibility in students towards the environment. By incorporating environmental education into the civic education curriculum, the moral, cognitive, and participatory dimensions of civic responsibility that depend on ecology (ecological citizenship) will be formed. Therefore, the climate crisis, especially in learning activities that implement integrated civic education with the environment.